A Cross-cultural, Intergenerational Activity: "Experience, Learn and Have Fun… Learning Journey": Program Profile. Issue 2 (2nd April 2020) - Lai, Alan; Jian-yun He, Lesley
ABSTRACT: Intergenerational study tourism (IST) is a conceptual model designed to promote cross-cultural, intergenerational (IG) encounters through travel and learning. IST is an area of IG practice that would benefit from further research. In response to this identified need, this paper documents a pilot effort to develop a model that includes the design of a cross-cultural, intergenerational activity and examines its perceived benefits, reflection and discussion. Participants in this pilot project represented different generations from local and international communities. To facilitate participant engagement, ice-breaking games and mission-oriented interventions were employed.